Pregnancy complications associated with maternal near-miss in an undeveloped province in south-central China, 2012–2022 - Xu Zhou; Yinglan Wu; Jie Gao; Xiaoying Chen; Aihua Wang; Junqun Fang (BMC Public Health)
Abstract Objective To explore the relationship between pregnancy complications and maternal near-miss (MNM). Methods Data were obtained from the Maternal Near-Miss Surveillance System in Hunan Province, China, 2012–2022. The MNM ratio refers to the number of MNM per 1000 live births, and maternal mortality refers to the number of maternal deaths per 100,000 live births. Chi-square trend tests (χ 2 trend) were used to determine trends in proportions by year. Multivariate logistic regression analysis (method: Forward, Wald, α = 0.05) and adjusted odds ratios (aORs) were used to identify risk factors for MNM. Results Our study included 780,359 women with 731,185 live births, a total of 2461 MNMs, and 52 maternal deaths were identified. The MNM ratio was 3.37‰ (95%CI: 3.23–3.50), and the maternal mortality was 7.11 per 100,000 live births (95%CI: 5.18–9.04). Coagulation/hematological dysfunction was the most common cause of MNM (75.66%). From 2012 to 2022, the proportion of coagulation/hematological dysfunction among MNM increased from 49.14% in 2012 to 86.39% in 2022, which was the only cause of MNM that showed an increased trend (χ 2 trend = 7.43, P = 0.01). Results of multivariate logistic regression analysis showed that 10 pregnancy complications were risk factors for MNM: hemorrhage disorder (aOR = 21.50, 95%CI: 19.64–23.54), infections (aOR = 1.91, 95%CI: 1.64–2.22), hypertension (aOR = 4.50, 95%CI: 4.08–4.98), heart disease (aOR = 14.96, 95%CI: 11.51–19.44), embolic disease (aOR = 171.70, 95%CI: 94.08-313.36), liver disease (aOR = 1.54, 95%CI: 1.25–1.90), anaemia (aOR = 4.72, 95%CI: 4.29–5.19), renal disease (aOR = 5.44, 95%CI: 4.00-7.40), pulmonary disease (aOR = 14.85, 95%CI: 8.33–26.50), and connective tissue disease (aOR = 5.15, 95%CI: 3.06–8.66). Conclusion The MNM ratio was relatively low in Hunan Province. Several pregnancy complications increased the risk of MNM. It is helpful for clinical counseling and public health policies, which may contribute to preventing MNM.